Association of the programmed death ligand‐1 combined positive score in tumors and clinicopathological features in esophageal cancer. Issue 4 (24th December 2021) - Huang, Ziling; Jin, Yan; Cai, Xu; Chen, Lijun; Shen, Xuxia; Li, Bin; Chen, Haiquan; Li, Yuan
Abstract: Background: The combined positive score (CPS) of the programmed death ligand‐1 (PD‐L1) 22C3 assay is a predictive marker of pembrolizumab monotherapy for advanced esophageal cancer (EC) patients. However, little is known about the association of the PD‐L1 22C3 CPS with the clinicopathological features and heterogeneity of PD‐L1 expression in EC in the Chinese population in a real‐world setting. Methods: We examined the association of the PD‐L1 22C3 CPS with clinicopathological characteristics in 533 EC specimens. Further, we compared 37 cases' different blocks of the same specimen and 50 paired primary/metastatic lymph node lesions to investigate the heterogeneity of PD‐L1 expression. Results: PD‐L1 positive expression was observed in 45.0% of 533 EC patients, including 46.8% with squamous cell carcinoma, 15.4% with adenocarcinoma, 28.6% with basaloid squamous carcinoma, 42.9% with spindle cell carcinoma, and 33.3% with neuroendocrine tumors. PD‐L1 positive expression was positively associated with lymph node metastasis (59.2% chance, p = 0.021) and venous/lymphatic invasion (66.3% chance, p = 0.029). PD‐L1 expression was highly consistent in different paraffin blocks of the same surgically resected specimen (concordance rate: 86.5%, p = 0.000016) and a moderate consistency (concordance rate: 78.0%, p = 0.000373) for the primary and metastatic lymph node lesion comparison. Conclusions: This is a novel study which demonstrated a positive correlation between a high PD‐L1 22C3 CPS and invasion/metastasis risk in EC surgical specimens. Both paired blocks and paired primary/metastatic lymph node lesions showed significant concordance. PD‐L1 heterogeneity was inferred to be mainly related to positive mononuclear inflammatory cells (MICs), which might have substantial implications for clinical practice. Abstract : The combined positive score (CPS) of the programmed death ligand‐1 (PD‐L1) 22C3 assay is a predictive marker of pembrolizumab monotherapy for advanced esophageal cancer (EC) patients. We examined the association of the PD‐L1 22C3 CPS with clinicopathological characteristics in 533 surgically resected EC specimens. Further, we independently compared 37 cases' different paraffin blocks of the same surgically resected specimen and 50 paired primary/metastatic lymph node lesions to investigate the heterogeneity of the PD‐L1 expression. PD‐L1 positive expression was positively associated with the presence of lymph node metastasis (59.2% chance, p = 0.021) and venous/lymphatic invasion (66.3% chance, p = 0.029). PD‐L1 expression was highly consistent in different paraffin blocks of the same surgically resected specimen ( p = 0.000016) and a moderate consistency ( p = 0.000373) for the primary and metastatic lymph node lesion comparison. This is the novel study to demonstrate a positively correlation between a high PD‐L1 22C3 CPS and invasion/metastasis risk in EC surgical specimens. Both paired blocks and paired primary/metastatic lymph node lesions showed significant concordance.